The Effect of Company Size, Capital Structure, and Profitability on Company Value Moderated by Dividend Policy - Wahyu Diana; Agus Munandar (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to determine the influence of company size, capital structure, profitability on company value with dividend policy as moderation. This research uses associative and quantitative methods. The real estate sector is the population in this research and the sample population is determined using predetermined standard criteria. The sample was obtained from the financial reports of the real estate sector on the Indonesia Stock Exchange for the 2018-2022 research period. Purposive sampling technique was used in this research, with test equipment using SPSS version 26. The test results show that company size has a positive influence, profitability has a significant positive influence on company value. Capital structure has a negative and significant impact on company value. Furthermore, dividend policy strengthens the influence of profitability on company value, then dividend policy cannot moderate company size and capital structure on company value, and dividend policy strengthens profitability on company value. Simultaneously the independent variable on the dependent has a significant influence of 73.5% and other variables influence the dependency. The decision that was approved at the GMS was to pay dividends every accounting period to shareholders, which will affect the company's future value. To gain investor trust, company value is taken into consideration in making decisions